2019
DOI: 10.1002/cncy.22139
|View full text |Cite
|
Sign up to set email alerts
|

A large series of hyalinizing trabecular tumors: Cytomorphology and ancillary techniques on fine needle aspiration

Abstract: BACKGROUND:Hyalinizing trabecular tumors (HTTs) are rare, essentially benign, follicular cell-derived thyroid neoplasms characterized by a trabecular growth pattern and nuclear pseudoinclusions. Their cytological findings are misleading, because these tumors are often misinterpreted on fine needle aspirate cytology as malignant lesions, such as papillary thyroid cancer and/or medullary thyroid cancer, leading to unnecessary total thyroidectomy. The aim of this study was to analyze the cytomorphological feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…The challenges to solving the problem of presurgical diagnostics are 3‐fold: First, some of the key cytologic features of PTC and medullary thyroid carcinoma, such as enlarged oval nuclei, nuclear grooves, and intranuclear pseudoinclusions, are typically seen in HTT (Fig. ) . Tabulation of the cytology diagnoses standardized into the Bethesda System for Reporting Thyroid Cytopathology showed that 42.1% and 26.4% of HTT cases were diagnosed on FNA as suspicious for malignancy (Bethesda V) and malignant (Bethesda VI), respectively (Table ), which often triggered total thyroidectomy.…”
Section: Cytologic Challenges Resulting From Httmentioning
confidence: 99%
See 1 more Smart Citation
“…The challenges to solving the problem of presurgical diagnostics are 3‐fold: First, some of the key cytologic features of PTC and medullary thyroid carcinoma, such as enlarged oval nuclei, nuclear grooves, and intranuclear pseudoinclusions, are typically seen in HTT (Fig. ) . Tabulation of the cytology diagnoses standardized into the Bethesda System for Reporting Thyroid Cytopathology showed that 42.1% and 26.4% of HTT cases were diagnosed on FNA as suspicious for malignancy (Bethesda V) and malignant (Bethesda VI), respectively (Table ), which often triggered total thyroidectomy.…”
Section: Cytologic Challenges Resulting From Httmentioning
confidence: 99%
“…Third, the relative rarity of HTT has limited the opportunity for general cytopathologists to become proficient in recognizing the key cytologic features this entity. Although the exact incidence is not known, the finding that 11 of 26 reports (42%) documenting the cytology of HTT are individual case reports is likely a reflection of its rarity . Therefore, heightened awareness of the subtle cytologic features of HTT and the availability of novel, specific molecular markers are important in the presurgical identification of this neoplasm.…”
Section: Cytologic Challenges Resulting From Httmentioning
confidence: 99%
“…16,30 BRAF and RAS mutations, which are common in PTC and follicular variant of PTC (FVPTC), respectively, have not yet been discovered in HTT. 16 However, Dell’Aquila et al 18 found a wild type BRAF V600E in all of their reported HTT cases.…”
Section: Discussionmentioning
confidence: 96%
“…2,16 The cytopathological diagnosis of HTT remains challenging as it displays some cellular characteristics similar to PTC. 17 Despite HTT exhibiting several unique cytomorphological traits such cellular aggregates within hyaline matrix, no papillary formations, low nuclear to cytoplasmic ratio, and fine chromatin, 18 both HTT and PTC can exhibit hypercellularity, and cellular atypia including nuclear clearing, grooves, and pseudoinclusions on FNA. 13,19,20 However, the accurate diagnosis of HTT is critical as it guides the course of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation